Outcome of Mid 1/3rd Clavicular Fracture After Open Reduction and Internal Fixation (Journal of Pakistan Orthopaedic Association, 2014)
Aim: To assess functional outcome after open reduction and internal fixation of clavicaular fracturesMethods: This is a prospective cohort study of ORIF (Open reduction and internal fixation) of middle 1/3rdclavicular fracture of patients who met the strict criteria for internal fixation of clavicular fractures. We had 9 patients from Feb 2010- November2012 who underwent the procedure. The patients were followed at 2 weeks, 6 weeks and 3 months after surgery. If there was any complication, the patients were followed till resolution of symptoms. The functional out come was measured using Quick DASH score, union rate, return to function and surgery related complications.Results: Outcome was measured using Quick DASH score (The Disabilities of the Arm, Shoulder and Hand questionnaire) at 2 weeks,6 weeks and 3 months follow up. Out of nine cases, one patient lost to follow up and remaining eight cases were followed. There was no case of non-union/ delayed union at three months. There was significant improvement in the Quick DASH score from 2 weeks to 3 months. The mean score after 2 weeks was 59.9 (Range 50-75) after 6 weeks 24.1 (range 20.5-29.5) and at 12 weeks post op 5.1( range 2.3-6.8) Three cases had temporary hypoesthesia, which resolved spontaneously and in one of these cases there was hypertrophic scar, which was managed conservatively.Conclusion: Although traditionally, non-operative treatment has been the mainstay of treatment for mid 1/3rdclavicular fractures however in certain selected patients and in certain fracture configuration, there is higher incidence of inadequate outcome in terms of union rate, cosmesis and functional ability if treated conservatively. In these patients, ORIF is a viable option to minimize the poor outcome